Perturbation of interactome through micro-RNA and methylome analysis in diabetes endophenotypes: the PIRAMIDE pathogenic clinical study design - Benincasa, Giuditta; Marfella, Raffaele; Schiano, Concetta; Napoli, Claudio (International Journal of Clinical Trials, 2019)
Background: The main challenge in type 2 diabetes (T2D) is to detect the regulators of pathogenic events during early stages of disease, as well as prevention and progression follow-up of cardiovascular (CV) complications. DNA methylation and micro-RNAs (miRNAs) are major components of the epigenome, which are involved in the diabetic interactome. This study protocol may contribute to advance our knowledge on molecular basis underlying T2D and its CV complications, as well as provide putative useful prognostic biomarkers. Methods: The perturbation of interactome through micro-RNA and methylome analysis in diabetes endophenotypes: the PIRAMIDE pathogenic clinical study protocol is a cross-sectional research program planned to combine big data and network-based analysis aimed to investigate whether DNA methylation and miRNAs may act as simultaneous regulators of the interactome in T2D patients. Clinical datasets will be aggregate to large-scale DNA methylation, mRNA-Seq, and miRNA-Seq analysis performed both on purified CD4+ and CD8+ T cells isolated from 35 T2D patients and 35 sex and age-matched controls. DNA methylome data will be used as input for the weighted human DNA methylation PPI network (WMPN) algorithm. RNA sequencing data will be used as input data for the TargetScan algorithm. The primary endpoint will be to integrate both DNA methylation and miRNA networks to potentially capture which genes are simultaneously modulate by interactions between epigenetic changes. Then, statistical analysis will be performed to correlate these molecular modifications with development of T2D-related CV complications. Conclusions: PIRAMIDE pathogenic clinical study protocol will test the hypothesis that simultaneous interactions between DNA methylation and miRNAs may hit T2D-associated candidate genes and predict the development of T2D-related CV complications. Trial Registration: The ongoing PIRAMIDE pathogenic clinical study protocol has been registered on NIH website (NCT03792607).